2018
DOI: 10.21873/invivo.11305
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-treated Asparagus Extract Down-regulates Heat Shock Protein 27 of Pancreatic Cancer Cells

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…The contact angles are much less than 90°. It certifies that the Fe‐MOF is with strong hydrophilicity, which is advantageous for the formation of water continuous emulsions 51,52 …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The contact angles are much less than 90°. It certifies that the Fe‐MOF is with strong hydrophilicity, which is advantageous for the formation of water continuous emulsions 51,52 …”
Section: Resultsmentioning
confidence: 96%
“…It certifies that the Fe-MOF is with strong hydrophilicity, which is advantageous for the formation of water continuous emulsions. 51,52 3.5 | Morphology of MOF-containing poly(HIPE) monoliths Figure 2). 16 The addition of PVA before polymerization is critical because the addition of organic monomers and the increase of temperature will reduce the stability of the emulsion.…”
Section: Mechanism For Mof-stabilized Hipesmentioning
confidence: 99%
“…Although various therapies have been developed against cancer, including chemotherapy, radiation therapy, and so forth, pancreatic cancer is still deadly and represents 10% of the five-year survival rate [75]. Resistance is known to occur in gemcitabine treatment, which is the most common anti-cancer drug [76,77]. The drug resistance makes gemcitabine ineffective, and it consequently leads to difficulties in the successful treatment of cancer.…”
Section: Resistance Inhibiting Natural Productsmentioning
confidence: 99%
“…CSCs, pancreatic cancer stem-like cells; RAGE, receptor for advanced glycation end products; c-PARP, cleaved-poly ADP ribose polymerase; Bax, Bcl-2-associated X protein; NF-κB, nuclear factor kappa B; Bcl-2, B-cell lymphoma-2; COX-2, cyclooxygenase-2; ABCB1, ATP-binding cassette B1; ABCG2, ATP-binding cassette G2; HSP27, heat-shock protein 27; p-JNK, phosphorylated c-Jun N-terminal kinase; PDK1, pyruvate dehydrogenase kinase 1; AKT1, protein kinase B1; CDk4, cyclin-dependent kinase 4; RRM1, ribonucleotide reductase subunit M1; RRM2, ribonucleotide reductase subunit M2; EpCam+, epithelial cell adhesion molecule+; ↑-up-regulation; ↓-down-regulation. Enzyme-treated asparagus extract (ETAS) is known to induce heat-shock protein (HSP) 70 [77]. Shimada et al investigated the regulation effect of ETAS on HSP27, which was previously demonstrated to causes gemcitabine resistance.…”
Section: Resistance Inhibiting Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation